Syngenta Enhanced Feed Corn (Enogen) Containing an Alpha Amylase Expression Trait Improves Feed Efficiency in Growing Calf Diets - M. A. Johnson; T. J. Spore; S. P. Montgomery; C. S. Weibert; J. S. Garzon; W. R. Hollenbeck; R. N. Wahl; E. D. Watson; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:To determine the response of growing calves when fed Enogen Feed (Syngenta) corn, containing an alpha amylase expression trait. Description:A total of 384 English crossbred steers having an average weight of 538 lb and originating from Texas were used to determine the effects on performance when fed Enogen Feed corn as either whole shelled or processed as dry-rolled at ad libitum intake. The Bottom Line:When fed in an ad libitum fashion to growing calves, Enogen Feed corn improves feed efficiency of growing calves by 5.50%.
Keywords: corn; alpha amylase; growing calf